Public value road infrastructure maintenance - Rifai, Ifan; Hernanda, Willi Pranata; Hidayat, Moh Taufik; Heryanto, Yanto (Indonesian Journal of Multidisciplinary Science, 2024)
This research aims to understand the public value of road infrastructure maintenance in Cirebon City. This research is of a quantitative descriptive type. The findings of the study show (1) that the maintenance of road infrastructure in Cirebon City has been effectively implemented. The community's assessment of road maintenance in Cirebon City based on their answers, views, knowledge, and attitudes shows satisfaction. (2) Public value is the government's public value to the community in serving the community correctly and being satisfied with the service system from the government, getting the quality that customers or consumers want is satisfied with what they want. How can the community assess the services provided. (3) The highest average value of the public value is indicator 10, which is related to "many road infrastructures that are only left damaged and not in order" which obtained an average value of 0.94% which is on the criteria that are quite good. While the smallest indicator is indicator 5, which is related to "whether the maintenance of road infrastructure is in accordance with what has been planned" with an average value of 0.73%, which is included in the category of quite good.